THE NEED TO DEVELOP LEARNING VIDEOS TO SUPPORT INDONESIA’S2013 CURRICULUM-BASED VOCATIONAL OFFICE ADMINISTRATION SUBJECTS - Sulistyaningrum, C. Dyah; Rahmanto, Andre N.; Wirawan, Arif Wahyu; Atma Dirgatama, Chairul Huda (Jurnal Vokasi Indonesia, 2020)
Teachers are expected to improve their professionalism by developing learning media that are able to facilitate students in learning according to their own abilities and in improving their competency. This research aims to describe the use of learning videos in teaching Office Administration subjects, especially mail competency and archiving. Direct interviews, observations, and a survey questionnaire provided data on the use of learning videos. The result showed that 1) learning videos are under-utilized as sources in learning the archiving process: textbooks and lectures are the most common forms today, and 2) learning video should be developed to learn about archiving and out basic mail competency.